The farthest shore an anthology of fantasy fiction from the Philippines - Alfar, Dean Francis; Nacino, Joseph Frederic F. (Quezon City The University of the Philippines Press, 2013)
Fantasy short stories.
In English.
Keywords: Fantasy fiction